La mujer educadora en los entornos del siglo XXI - Gadea Rubio, Olga Cecilia (2012)
Speaking of women and education has been andis a challenge to describe in a few pages. Thepresent article aims to summarize some of thebenefits and challenges of the XXI century womaneducator faces. Situations of her environment as themaelstrom of the knowledge society, technologyand the reproach of values in young people andremember the happiness in their lives and especiallyin their classrooms are some of the topics coveredin the following lines, for strokes and experiences.